1980
DOI: 10.1073/pnas.77.11.6443
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of small oligonucleosomal chains into 300-A globular particles.

Abstract: Chicken erythrocyte oligonucleosomes (trimers to about 20-mers) are able to interact with each other through the very Iysine-rich histones (HI and H5) and form heterogeneous globular particles with a mean diameter of about 300 A. These particles assemble spontaneously during micrococcal nuclease digestion of chromatin in the presence of 30 mM NaCl and contain approximately 25 nucleosomes. They are sensitive to ionic strength and unfold at lower salt concentrations but can be reconstituted by restoring the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…The pvesence of an assembly barrier has alio been supoested by Jorcano et a1 (18). These author5 showed that particles containinp about 25 nucleosomes were fnrmpd hv an aaareaation of oliaanuclkosomes in the sire ranme of trimers UD to .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The pvesence of an assembly barrier has alio been supoested by Jorcano et a1 (18). These author5 showed that particles containinp about 25 nucleosomes were fnrmpd hv an aaareaation of oliaanuclkosomes in the sire ranme of trimers UD to .…”
Section: Discussionmentioning
confidence: 97%
“…It has been peported t h a t t h e H1, H5 molecules accumulate on -, and s t a b i l i s e t h e m a t e r i a l present w i t h i n , t h e f a s t sedimentina peak of t o t a l n u c l e a r e x t r a c t s (11,12,14,18,20,21). Therefore we t r i e d t o q i a n t i t a t e t h e amount of l y s i n e -r i c h h i s t o n e s present on our assembly products.…”
Section: Involvement Of T H E L Y S I N E -R I C H H I S T O N E S I mentioning
confidence: 99%
See 2 more Smart Citations
“…Chromatin soluble in digestion buffer (ionic strength "70 mM) but insoluble at physiological ionic strength (I chromatin) was broken down to mononucleosomes that were insoluble in digestion buffer (Fig. 2) Jorcano et at (29) have recently reported a study on chicken erythrocyte bulk chromatin. Extensive nucleolysis ofbulk chromatin at 370C resulted in two main fractions: mono-and dinucleosomes that did not aggregate and were deficient in the lysine-rich histones H1 and H5 and oligonucleosomes (3 c R < 8) that contained an excess of lysine-rich histones and were capable of associating into globular particles containing 25-29 nucleosomes.…”
mentioning
confidence: 99%